2018
DOI: 10.1186/s12935-018-0621-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long non-coding RNA competing interactions and biological pathways associated with prognosis in pediatric and adolescent cytogenetically normal acute myeloid leukemia

Abstract: BackgroundLncRNAs can regulate miRNAs and mRNAs by sequestering and binding them. Indeed, many researchers have reported lncRNA mediated-competing endogenous RNAs (ceRNAs) could regulate the progression of solid tumors. However, the roles of ceRNA in acute myeloid leukemia (AML), especially in pediatric and adolescent AML, were not completely expounded.Materials and methods27 cytogenetically normal acute myeloid leukemia (CN-AML) patients under 18 years old with corresponding clinical data were selected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
(55 reference statements)
3
21
0
Order By: Relevance
“…On the one hand, MEG3 is upregulated in APL (122), whereas in AML cell lines, it was found to function as a tumor suppressor (123). On the other hand, TCGA analysis revealed that CRINDE is downregulated in APL (122) and upregulated in bone marrow stem cells (124), bone marrow samples and AML cell lines (125). This could be attributed to the fact that the AML cell lines were harvested from patients with other AML subtypes or due to differences in gene expression analysis.…”
Section: Current Research On Long Non-coding Rnas In Myeloid Malignanmentioning
confidence: 99%
“…On the one hand, MEG3 is upregulated in APL (122), whereas in AML cell lines, it was found to function as a tumor suppressor (123). On the other hand, TCGA analysis revealed that CRINDE is downregulated in APL (122) and upregulated in bone marrow stem cells (124), bone marrow samples and AML cell lines (125). This could be attributed to the fact that the AML cell lines were harvested from patients with other AML subtypes or due to differences in gene expression analysis.…”
Section: Current Research On Long Non-coding Rnas In Myeloid Malignanmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are confined to transcripts lacking significant ORFs with more than 200 nt in length, which play important roles in tumorigenesis in progression of disorders, including AML [3]. Moreover, lncRNAs have been reported to be associated with prognosis of AML by functioning as competing endogenous RNAs (ceRNAs) [4]. Previous studies have reported that lncRNAs are implicated in AML progression by regulating cell processes, including proliferation, apoptosis, migration, invasion and differentiation [5][6][7].…”
mentioning
confidence: 99%
“…Since mir-23b and mir-27b belong to the same family, the expression levels of the two miRNAs also showed a very high positive correlation. Several lncRNAs have been identified as the signatures of prognosis or tumor recurrence, such as AC092811.1, LINC00326, and C20orf197 ( Yin et al, 2018 ; Zhu et al, 2019 ; Zhao et al, 2020 ). The correlation between miRNA and lncRNA is weaker in the TME with a worse prognosis than the TME with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%